A Dynamic Time Scale Approach for On-line Measurement-Based Capacity Allocation - Haciömeroglu, Fatih; Devetsikiotis, Michael (Journal of Communication and Information Systems, 2017)
Cunent high-speed networks handle a variety of services, requiring different QoS constraints. The choice of appropriately accurate but also practically implementable measurement algmithms in this context becomes crucial. In this paper, we perform a comparative study of alternative on-line bandwidth allocation algorithms, we analyze their complexity, and petf01m comparisons via simulation experiments. Moreover, we argue the relevance of a dynamic measurement time scale approach and demonstrate the effectiveness of this new approach over the static one. Our motivation is to use these algorithms in the data plane of "’self-sizing" frameworks, and make use of their output in taking control plane decisions either locally or globally, in an on-line fashion. Previously, no such comprehensive comparison of relevant methods has been carried out, especially from a combined accuracy versus implementation complexity point of view and from the perspective of changing the measurement time scale "dynamically".